Mothers As Learning Agent: Empowering Community Groups for Educational Independence in Kepetingan Hamlet - Ferdiansyah, Dani; Andayani, Endah Alamsari; Prasetyo, Yudy (LPPM Universitas Jenderal Achmad Yani, 2025)
This study aims to examine the role of mothers as learning agents in Kepetingan Hamlet and to analyze the strategies and forms of empowerment activities they implement. Limited access to formal education caused by geographical, economic, social, and cultural factors has encouraged mothers in this area to take an active role by initiating and implementing community-based learning activities. This study employed a qualitative method using a community-based research approach. Data were collected through in-depth interviews, participant observation, and documentation. The findings identify four main forms of mothers’ contributions: (1) the establishment of learning communities to expand children’s access to education, (2) the utilization of external support, including student community service programs, (3) effective time management in balancing domestic responsibilities and educational roles, and (4) creativity in utilizing local media as learning tools. These results indicate that mothers’ roles extend beyond that of learning companions to include functions as facilitators, innovators, and drivers of community-level learning activities. Such roles not only contribute to improving the quality of children’s learning but also promote women’s empowerment and strengthen social solidarity. Thus, mothers play a significant role in fostering educational self-reliance and transforming community-based societies.